Inisiasi Pembangunan Lembaga Kursus dan Pelatihan di Pondok Pesantren Aufia Global Islamic Boarding School sebagai Solusi Kompetensi Teknik Instalasi PLTS bagi Remaja Putus Sekolah - Rosma, Iswadi Hasyim; Putra, Agus Ika; Jamaan, Ahmad; Ali, Nurhalim Dani; Suwitno, Suwitno (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2024)
The Aufia Global Islamic Boarding School (PP AGIBS) is in the village of Minas Jaya, Minas District, Siak Regency, Riau Province. The PP AGIBS curriculum emphasizes Islamic education, so it contains little in the way of science and technology competencies, such as Solar Power Plant Installation Engineering. (PLTS). In general, the village of Minas Jaya is around the former PT Chevron Pacific Indonesia, which used to be the largest oil mining company in Riau Province, and most of its residents worked at Chevron as unskilled laborers, such as cleaning staff and security personnel. The presence of PP AGIBS is very strategic considering its location around the community; however, PP AGIBS has a moral responsibility to contribute to the social issues faced by the community in the Minas Jaya village. Therefore, PP AGIBS needs to collaborate well with the University of Riau and the Minas Jaya village government to facilitate communication with the residents of Minas Jaya on issues outside the scope of Islamic studies, such as the high dropout rate among teenagers. One of the solutions implemented to address the issue of school dropouts is the initiation of the AGIBS Taruna Course and Training Institute (LKP) development. To realize the initial steps of this LKP development, several activities and role distributions were carried out. Among them, PP AGIBS contributes as the provider of infrastructure, including location, office space, office supplies, and other related facilities, while the service implementation team from Riau University provides human resources as instructors and supplies training equipment for PLTS installation techniques. With the synergy between Riau University and PP AGIBS, it is hoped that school dropouts can gain competence in the field of PLTS installation techniques.